Colour Order. (September 2019) - Koenderink, Jan; van Doorn, Andrea; Gegenfurtner, Karl
Scrambled hue circles with a resolution ranging from 6 steps to 60 steps were presented on a varicoloured background. The hue steps were presented as mutually non-contiguous "chips, " small circular disks, placed uniformly on a large circle. The task was to sort the chips with respect to their hue. Participants generally manage to sort a 24-step hue circle faultlessly but commit many ordering reversals (also of several steps, up to five) on sorting a 60-step hue circle. The pattern of local reversals of chips depends on the hue region. The findings are relevant for the design of user interfaces for various types of applications, such as colour pickers or graphical design, that rely onrgb screen colours as the available palette.